Phosphorus and Bacillus subtilis in absorption and removal of micronutrients in Phaseolus vulgaris L. - Ruelas-Islas, Jesús del Rosario; Romero-Félix, Celia Selene; Mendoza-Pérez, Cándido; Núñez-Ramírez, Fidel; Rocha Santillano, Jessica Janeth; Ayala-Armenta, Quintín Armando (Revista Mexicana de Ciencias Agrícolas, 2022)
Common bean (Phaseolus vulgaris L.) is a very important legume that is part of the diet in Latin America and other countries. In northern Sinaloa, Mexico, the yield of this crop is mainly affected by management practices (irrigation and fertilization dose) and variability in climate. An experiment was established in the Fuerte Valley, north of Sinaloa, Mexico, with the purpose of researching the response of bean culture to different doses of phosphorus [(P) (0, 25, 50, 100 kg ha-1 P2O5)] and the influence of the Bacillus subtilis Q11 (Bs) strain on the absorption and removal of micronutrients. The experiment consisted of plots divided into randomized complete blocks with three repetitions. According to the results obtained, the doses of P significantly influenced the absorption of micronutrients in the following preferential order Fe> Mn> Zn> B> Cu. While inoculation with Bs increased the absorption process with respect to non-inoculated plants.